THE FUTURE OF EDUCATION IN THE DIGITAL ERA: BETWEEN TECHNOLOGICAL INNOVATION AND EQUITABLE ACCESS - Annisa Tri Ananda Dewi; M. Syafiih (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Advances in information and communication technology (ICT) have had a significant impact on the education system, including in Indonesia. Learning can now take place without the constraints of time and space through the use of online platforms, digital classrooms, and the application of cutting-edge technologies such as the Internet of Things (IoT), blockchain, and the metaverse. However, expanding access to technology has not fully aligned with improving the quality of education. Digital inequality remains a major issue, encompassing limitations in network infrastructure, device availability, and the ability of educators and students to utilize technology optimally. The purpose of this article is to examine how technology is transforming education, considering aspects of access and equity; to examine their interrelationships; and to examine the implications for education. and suggests approaches to make technology-based education more inclusive and equitable. This study uses a descriptive approach to examine the relationship between justice, technology, and educational quality, based on the perspectives of several researchers, such, The results of the discussion indicate that educational technology is not entirely neutral, as it contains specific values, interests, and power structures. Therefore, the application of justice-oriented technology pedagogy needs to be developed so that educators are able to understand and assess technology not only from a functional perspective but also from its social and ethical implications. To realize a just and sustainable digital educational transformation, a comprehensive strategy is needed, including improving teacher competency, equitable distribution of technological infrastructure, providing open learning resources, and cross-sectoral collaboration between the government, higher education institutions, and technology providers. Thus, technology can play a role as an instrument to strengthen justice, quality, and inclusiveness in education in Indonesia.